THE EFFECT OF FACILITIES ON TOURISTS’ REVISIT INTENTION AT THE MARITIME MUSEUM, JAKARTA - Meliani, Rindi; Gantina, Devita; Nurmalinda, Elda (J-TRUE: Journal of Travel and Leisure, 2025)
The Jakarta Maritime Museum is an educational tourism destination based on maritime history that plays an important role in preserving Indonesia’s maritime values. However, suboptimal facility conditions may affect tourists’ intention to revisit the museum. This study aimed to analyze and measure the effect of facilities on tourists’ revisit intention at the Jakarta Maritime Museum. A quantitative descriptive approach was employed using a survey method. The research population consisted of tourists who had previously visited the Jakarta Maritime Museum, with a sample of 100 respondents determined using the Slovin formula and purposive sampling technique. Data were collected through observation and questionnaire distribution. The data were analyzed using validity and reliability tests, descriptive statistical analysis, correlation coefficient analysis, coefficient of determination analysis, simple linear regression, and hypothesis testing (t-test) with the assistance of SPSS version 27. The results indicated that facilities had a significant effect on tourists’ revisit intention at the Jakarta Maritime Museum. The coefficient of determination value of 0.850 showed that facilities accounted for 85% of the variation in revisit intention, while the remaining percentage was influenced by other factors outside this study. Therefore, it was concluded that improving the quality and adequacy of facilities is a crucial factor in encouraging tourists to revisit the Jakarta Maritime Museum. Keywords: Facilities; Revisit Intention; Museum; Tourists; Cultural Tourism